Acanthamoeba Species Keratitis in a Soft Contact Lens Wearer Molecularly Linked to Well Water. Issue 2 (1st April 2006) - Mubareka, Samira; Alfa, Michelle; Harding, Godfrey K; Booton, Gregory; Ekins, Marilyn; Caeseele, Paul Van
Abstract : Acanthamoeba species keratitis has been associated with soft contact lens wear. In the present report, an epidemiological link was established between the patient's isolate and well water from the home using molecular methods. To the authors' knowledge, this is the first case in Canada where such a link has been established. Primary care practitioners and specialists, including ophthalmologists and infectious diseases specialists, must maintain a high degree of clinical suspicion in soft contact lens wearers with keratitis unresponsive to conventional topical and systemic treatment.